Reflections on Enhancing Speaking Skills: An Autobiographical Narrative of Teaching Practice in a Private English Tutorial - Dini Khoirina; Dewi Rochsantiningsih; Kristian Adi Putra (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the role of reflective practice in enhancing the teaching of speaking skills within a private English tutorial context. Despite growing recognition of reflective teaching, limited research addresses its application in one-on-one tutorial settings. Adopting an autobiographical narrative approach, the researcher employed Cirocki and Widodo’s (2019) reflective framework and Gibbs’ reflective cycle (1988) over a three-month period. Data were collected through personal teaching diaries and audio recordings of lessons with two intermediate-level students. Structured reflection positively influenced lesson planning, in-class adjustments, and post-lesson evaluations. Student A, initially hesitant and disfluent, showed improved spontaneity and fluency. Student B, who struggled with confidence and vocabulary, demonstrated increased participation and lexical range. These improvements were closely tied to the teacher’s evolving responsiveness and student-centered strategies enabled by reflective practice. The findings suggest that reflective teaching supports better identification of student needs and fosters adaptive instructional methods. While the small sample size limits generalizability, the study underscores the value of integrating structured reflection into teaching routines. Reflective practice proved instrumental in enhancing both teacher development and student speaking outcomes in a private tutorial setting. Its application has practical implications for private tutors and language institutions, encouraging the integration of tools such as diaries and lesson recordings into teacher training to promote continual professional growth.